Fnr Negatively Regulates Prodigiosin Synthesis in Serratia sp. ATCC 39006 During Aerobic Fermentation - Sun, Di; Zhou, Xuge; Liu, Cong; Zhu, Jingrong; Ru, Yunrui; Liu, Weijie; Liu, Jiawen (Frontiers in Microbiology, 2021)
The well-known Crp/Fnr family regulator Fnr has long been recognized as an oxygen sensor to regulate multiple biological processes, including the switch between aerobic/anaerobic metabolism, nitrogen fixation, bioluminescence, infection, and virulence. In most cases, Fnr was found to be active under anaerobic conditions. However, its role in aerobic antibiotic metabolism has not yet been revealed. In this research, we report that in the model organism, Serratia sp. ATCC 39006, Fnr (Ser39006_013370) negatively regulates prodigiosin production by binding to the spacer between the −10 and −35 region in the promoter of prodigiosin biosynthetic gene cluster under aerobic conditions. Fnr was also shown to modulate the anti-bacterial activity and motility by regulating pathway-specific regulatory genes, indicating that Fnr acts as a global regulator in Serratia sp. ATCC 39006. For the first time, we describe that Fnr regulates antibiotic synthesis in the presence of oxygen, which expands the known physiological functions of Fnr and benefits further investigation of this important transcriptional regulator.